MOTIVASI DAN PENGALAMAN PENGGUNA SEBAGAI FAKTOR TAMBAHAN DALAM MENINJAU PENERIMAAN APLIKASI SELULER KAI ACCESS : MODIFIKASI TECHNOLOGY ACCEPTANCE MODEL (TAM) - Zulvia, Pepi; Shinta Yerina, Adinda (Jurnal Studi Komunikasi dan Media, 2023)
The increasingly sophisticated and rigorous development of technology and information currently means that service companies are required to be able to provide easy, fast, and precise services. As a service that is often used by the public, PT Kereta Api Indonesia (KAI) presents the only official application called KAI Access. This application is here with the aim of providing convenience and optimizing the services provided to consumers in purchasing train tickets. The evaluation and improvement process continues to be carried out by PT KAI for the optimal use of this application by the community. This research aims to review the acceptance of the KAI Access application used by the public by presenting additional factors of motivation and user experience as a modification of the Technology Acceptance Model (TAM) method. Respondents in this study were 120 people using accidental sampling techniques. The instrument used is a closed questionnaire which is technically given via an online media form. Data processing in the analysis utilizes the SEM-PLS approach. The results of the analysis show that the role of easy utilization provides motivation for consumers so that later it will give rise to the experience of willing to use the application.